Catastrophic Cervical Spine Injuries in Contact Sports. (November 2016) - Hutton, Michael James; McGuire, Robert A.; Dunn, Robert; Williams, Richard; Robertson, Peter; Twaddle, Bruce; Kiely, Patrick; Clarke, Andrew; Mazda, Keyvan; Davies, Paul; Pagarigan, Krystle T.; Dettori, Joseph R.
Study Design: Systematic review. Objectives: To determine the incidence of catastrophic cervical spine injuries (CCSIs) among elite athletes participating in contact team sports and whether the incidence varies depending on the use of protective gear or by player position. Methods: Electronic databases and reference lists of key articles published from January 1, 2000, to January 29, 2016, were searched. Results: Fourteen studies were included that reported CCSI in rugby ( n = 10), American football ( n = 3), and Irish hurling ( n = 1). Among Rugby Union players, incidence of CCSI was 4.1 per 100, 000 player-hours. Among National Football League players, the CCSI rate was 0.6 per 100, 000 player-exposures. At the collegiate level, the CCSI rate ranged from 1.1 to 4.7 per 100, 000 player-years. Mixed populations of elite and recreational rugby players in four studies report a CCSI rate of 1.4 to 7.2 per 100, 000 player-years. In this same population, the scrum accounted for 30 to 51% of total reported CCSIs in Rugby Union versus 0 to 4% in Rugby League. The tackle accounted for 29 to 39% of injuries in Rugby Union and 78 to 100% of injuries in Rugby League. Making a tackle was responsible for 29 to 80% of injuries in American football. Conclusion: CCSIs are infrequent among elite athletes. There is insufficient evidence to determine the effect of protective gear (e.g., helmets, padding) on CCSI incidence. Scrum and tackle in rugby and tackling in American football account for the majority of CCSIs in each respective sport.